The anatomy of ability and the limits of intelligence in Kant's philosophy - فەرەج, نەوزاد جەمال (Sulaimani Journal for Humanities, 2025)
This paper, introduce some essential points of Kant’s critical philosophy. Philosophy according to Kant should be first critical towards its own knowledge. Before any philosophical inquiry start, should the Reason be criticized and investigated. It is obvious that since Kant, philosophy took a critical direction. In addition, the Reason is in charge of philosophical critics. Nevertheless, before any attempts to save philosophy from any trouble, should reason, start with criticizing itself. Which should examines its limits and capabilities. Therefore, reason has double duty, criticizing itself and then delivering critics to any philosophical subjects.